2013
DOI: 10.1115/1.4024743
|View full text |Cite
|
Sign up to set email alerts
|

Performance Study of a Photovoltaic Thermal System With an Oscillatory Flow Design

Abstract: In this study, integrated photovoltaic thermal roofing system has been successfully built and tested to improve the photovoltaic efficiency as well as providing domestic hot water supply. The major components of the solar photovoltaic thermal (PV/T) collector in this study comprise of amorphous silicon solar cells arranged in series that were adhered to the roofing structure. Unified structure of copper tube absorbers with oscillatory flow configuration was attached to the back plate which was insulated with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In a similar study conducted for Bangkok city, Nualboonrueng et al [73] reported a payback time of 6.4 years, 11.8 years and 13.4 years for an a-Si, pc-Si and c-Si-based PVT system, respectively. Rahou et al [150] also confirmed a better cost/benefit ratio of a-Si based PVT systems over pc-Si. Axaopoulos et al [151] studied the commercially available PVT systems for three locations: (Athens, Munich and Dundee), using TRNSYS, and reported that the PVT system investment is more beneficial when the existing auxiliary heating system is powered by electricity instead of oil and natural gas.…”
Section: Economics Of Pvt and Cpvt Systemsmentioning
confidence: 85%
“…In a similar study conducted for Bangkok city, Nualboonrueng et al [73] reported a payback time of 6.4 years, 11.8 years and 13.4 years for an a-Si, pc-Si and c-Si-based PVT system, respectively. Rahou et al [150] also confirmed a better cost/benefit ratio of a-Si based PVT systems over pc-Si. Axaopoulos et al [151] studied the commercially available PVT systems for three locations: (Athens, Munich and Dundee), using TRNSYS, and reported that the PVT system investment is more beneficial when the existing auxiliary heating system is powered by electricity instead of oil and natural gas.…”
Section: Economics Of Pvt and Cpvt Systemsmentioning
confidence: 85%
“…The spiral flow design obtained the highest total efficiency of 68% and thermal efficiency of 50.12%, compared to the serpentine flow design with the lowest total efficiency of 45% and thermal efficiency of 32.35%, among the several designs considered [19]. A PV/T roofing system with amorphous silicon solar cells and oscillatory flow arrangement of tubes beneath the PV module produced an overall efficiency between 70.53% and 81.5% [142]. Aluminium box type channels underneath the PV module, provided better performance than fins, in a sheet and tube thermal absorber, and provided high combined efficiency [143].…”
Section: Sheet and Tube Absorbermentioning
confidence: 99%
“…The temperature becomes lower when the inlet size increases because the mass flow rate increases. When the heat flux is fixed, the increase in mass flow rate can cause a drop in temperature [25].…”
Section: Parameter 2: Inlet Sizementioning
confidence: 99%